How Does Policy Perception Affect Green Entrepreneurship Behavior? An Empirical Analysis from China - Fengdi Chu; Wei Zhang; Yuan Jiang (Discrete Dynamics in Nature and Society)
As sustainable development has become a worldwide concern in dealing with tensions between economic development and resource sustainability, green entrepreneurship as a potential solution is gaining popularity. This paper investigates the perceptions of green policies and their impact on green entrepreneurial behavior. Furthermore, green self-efficacy is identified as a psychological mechanism linking green entrepreneurship policies and green entrepreneur behavior and moral reflectiveness as a boundary condition. Building on the policy acceptance model (PAM), the relationships between two policy perceptions and two green entrepreneurial behaviors, the mediating effect of green self-efficacy, and the moderating effect of moral reflectiveness are explored. Results support the mediation and moderation effects, implying that governmental institutions can strive to improve entrepreneurs’ perceived usefulness and ease of use in terms of public policies to strengthen their engagement in green entrepreneurial behaviors.